Composition and distribution of NSO compounds in two different shales at the early maturity stage characterized by negative ion electrospray ionization coupled with Fourier transform ion cyclotron resonance mass spectrometry - Chang-Wei Ke (KeAi Communications Co., Ltd., 2018)
Abstract Gas chromatography/mass spectrometry (GC/MS) can only analyze volatile molecular compounds, and it has limitations when applied to determine the complex components of crude oils and hydrocarbon source rocks. Based on Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR-MS) and GC/MS analyses, the molecular compositions of NSO compounds in extracts from the Permian Dalong Formation, Sichuan Basin and the Permian Lucaogou Formation, Junggar Basin in China were compared. Analyses of types of heteroatoms present (S1, S2, S3, OS, OS2, O2S, NS, and NOS compounds) suggest that marine shales from the Dalong Formation are mainly composed of carboxylic acids (O2 compounds) with a high abundance of fatty acids, indicating a marine phytoplankton organic source. However, lacustrine shales from the Lucaogou Formation are dominated by pyrrolic compounds (N1 compounds) with abundant dibenzocarbazole. It suggests that the organic source materials may be derived from lower aquatic organisms and lacustrine algae. Overall, FT-ICR-MS has potential for applications in analyses and determination of depositional environments and organic sources in petroleum geology.